Three types of underdeveloped communities in Croatia: Latent, collapsed, and disorganized communities. Issue 5 (19th October 2020) - Opačić, Ana
ABSTRACT: Article proposes a typology of underdeveloped communities in Croatia based on types ofsocial change and dimensions of the community. The research isdesigned as a cross-case analysis with seven municipalities 10 represented by 29 experts in total. Three types of underdeveloped communities are recognized: latent communities have solid social fabric but do not have mobilized formal structures and are facing inertia as a type of social change; collapsed communities that have low capacity to handle incremental social changes or transitions; and disorganized communities that have faced dramatic social change and certain catastrophic events, have their structurere shaped, and struggle to organize a new community on the grounds of previous one. A common pattern that emerged between the cases is a lack of adequate community response to specific social change. All of these communities had difficulties in managinge conomic transition in early 90's and significant demographic changes reshaped existing lifestyles.